'Sex doesn't alarm me': Exploring heterosexual male identity in BBC's Sherlock. Issue 3 (1st October 2019) - Morgan, Ashley
Using the character of Sherlock Holmes in the recent BBC's Sherlock (2010–present), this article explores the challenges posed to masculine identity through ascetic behaviour. Asceticism is usually associated with abstinence from food and sexual behaviours for religious purposes, but is used on this occasion to describe a person who has little interest in sexual relationships of any kind. A preoccupation with working life, in this instance, detection, replaces the desire for sexual relationships. Sexual behaviours contribute greatly to masculine, heteronormative identity and men are often depicted on television engaging in sexual relationships, or desiring to do so. In Sherlock, Holmes's lack of interest in sex, despite many opportunities, is of interest as it fails to detract from his strong masculine identity. This article explores Holmes's homosocial relationship with John Watson, and suggests that an uneven sexual binary occurs when one character is resolutely straight and the other appears as pansexual. Holmes's masculinity is further ratified through his clothing, drug use, demonstrations of hyper-intellect and narcissism. While sex might be largely absent from this particular portrayal, masculinity is accounted for in these behaviours, which proposes that masculinity need not be predicted in overtly sexual behaviours and that asceticism is a viable form of sexual identity.